In Situ Real-Time Chemiluminescence Imaging of Reactive Oxygen Species Formation from Cardiomyocytes - Yunbo Li; Haiou Shen; Hong Zhu; Michael A. Trush; Ming Jiang; Ge Wang (International Journal of Biomedical Imaging)
We have applied the highly sensitive chemiluminescence (CL) imaging technique to investigate the in situ ROS formation in cultured monolayers of rat H9c2 cardiomyocytes. Photon emission was detected via an innovative imaging system after incubation of H9c2 cells in culture with luminol and horseradish peroxidase (HRP), suggesting constitutive formation of ROS by the cardiomyocytes. Addition of benzo(a)pyrene-1,6-quinone (BPQ) to cultured H9c2 cells resulted in a 4-5-fold increase in the formation of ROS, as detected by the CL imaging. Both constitutive and BPQ-stimulated CL responses in cultured H9c2 cells were sustained for up to 1 hour. The CL responses were completely abolished in the presence of superoxide dismutase and catalase, suggesting the primary involvement of superoxide and hydrogen peroxide (H2O2). In contrast to BPQ-mediated redox cycling, blockage of mitochondrial electron transport chain by either antimycin A or rotenone exerted marginal effects on the ROS formation by cultured H9c2 cells. Upregulation of cellular antioxidants for detoxifying both superoxide and H2O2 by 3H-1,2-dithiole-3-thione resulted in marked inhibition of both constitutive and BPQ-augmented ROS formation in cultured H9c2 cells. Taken together, we demonstrate the sensitive detection of ROS by CL imaging in cultured cardiomyocytes.